家庭作為弱勢人群的首重保障: 儒家倫理與醫療倫理: The Family as the Primary Protector of the Vulnerable: Confucian versus Medical Ethics - LO, Ping Cheung (International Journal of Chinese & Comparative Philosophy of Medicine, 2013)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 晚近國際生命倫理學的個人主義色彩仍然甚濃，本文以如何保護醫療弱勢人群（病人）為例，指出國際生命倫理委員會2009年報告書這方面的弊病。文中一方面解釋了儒家倫理學的“家庭共決” 模式，為何應當作為保護醫療弱勢人群的首重保障，另方面也梳理出其它價值體系的相關觀點，發現某些西方學者也有類似看法，只是未為重視。筆者最後以香港公立醫院對終止維持生命治療及預設醫療指示的道德指引為例，說明儒家的家庭共決模式實際如何運作。 Individualism is still very much alive in “international” bioethics. Using two documents from the International Bioethics Committee as examples (Proposed Outline for a Report on Respect for Human Vulnerability and Personal Integrity, 2009; Report of the IBC on the Principle of Respect for Human Vulnerability and Personal Integrity, 2011), and focusing on hospital patients as a vulnerable group, this essay points out the pitfalls of individualistic bioethics. Confucianism advocates family co-determination rather than individual self-determination, and this model of decision making can serve as the first bulwark in protecting vulnerable patients. This model of medical decision making is not unique to Chinese culture, but is actually advocated by a small number of Western scholars. This essay also illustrates how family co-determination in medical decisions works using the example of two recent policies introduced in Hong Kong public hospitals, viz., forgoing life-sustaining treatment for the terminally ill and the use of advance directives. DOWNLOAD HISTORY | This article has been downloaded 342 times in Digital Commons before migrating into this platform.